The legal ratio of authority transfer from the capital market supervisory agency to the Financial Services Authority as a bankruptcy petitioner - Tata Wijayanta; Sheva Trisanda Adistia; Wahyudi Kurniawan; Rado Fridsel Leonardus; Bambang Eryanto Hermawan (Legality : Jurnal Ilmiah Hukum, 2025)
The article aims to analyse the legal ratio or legal reasons behind the transfer of authority from the Capital Market Supervisory Agency to the Financial Services Authority by qualitatively analysing the secondary data and presenting it in descriptive form. Regulation of bankruptcy applications for Securities Companies based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations may only be submitted by the Capital Market Supervisory Agency. This is because the Capital Market Supervisory Agency, based on Law Number 25 of 2007 concerning Capital Investment, is considered to understand the situation of Securities Companies. This authority is only given to the Capital Market Supervisory Agency to avoid bankruptcy applications submitted by creditors to securities companies. This is prevented because it could result in the securities company being bankrupted by creditors or shareholders. However, following the promulgation of Law Number 21 of 2011 concerning the Financial Services Authority, this authority was transferred to the Financial Services Authority from the Capital Market Supervisory Agency. The research used a normative research method supported by a statutory approach. This article found that the mechanism for bankruptcy applications for securities companies by the Financial Services Authority. Applications from Securities Companies or Creditors are addressed to the Executive of the Capital Market Supervisory Agency directly or via electronic mail to the Financial Services Authority electronic mail system, as regulated in the Regulation of Financial Services Authority Number 21 of 2022.